Tajdid Iman Al-Muslimin fi Qoryati Silandurung min Khilali Barnamij Khidmati Al-Mujtama' fi Syahri Ramadhon - Lubis, Hasan Hamzah; Suhendri, Suhendri (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
Learning Islamic sciences and the Quran profoundly influences individual and community faith renewal in various aspects. Employing a descriptive research approach, analyzing Quranic verses, prophetic sayings, and community leaders' opinions, a study conducted in Silandurong village during Ramadan revealed a lack of enthusiasm among its predominantly Muslim population for Islamic education and Quranic reading. Reasons include parental neglect in nurturing proper beliefs, societal indifference toward the illuminating religion, and governmental neglect of religious programs. Despite a Muslim majority, attendance at prayers and educational sessions barely reaches 5%, even during Ramadan. To address this, the researcher recommends the establishment of educational councils, memorization circles, and Islamic evening schools for children to revitalize faith and foster community well-being, promoting comfort, tranquility, stability, and security from harm.